Evaluation of Risk Factors for Laryngeal Squamous Cell Carcinoma: A Single-Center Retrospective Study - Zhang, Qihe; Wang, Huanhuan; Zhao, Qin; Zhang, Yuyu; Zheng, Zhuangzhuang; Liu, Shiyu; Liu, Zijing; Meng, Lingbin; Xin, Ying; Jiang, Xin (Frontiers in Oncology, 2021)
Background The survival rate of patients with laryngeal squamous cell carcinoma (LSCC) is correlated with several factors. However, the independent prognostic factors of patients with LSCC remain unclear. Thus, we sought to identify prognostic factors affecting LSCC outcomes in the Chinese population. Methods The survival and potential prognostic factors of 211 patients with LSCC between April 2011 and July 2019 were retrospectively analyzed. Overall survival (OS) and progression free survival (PFS) were estimated by the Kaplan Meier method, and a log-rank test was used to compare the possible prognostic factors between different groups. The Cox proportional hazard model was used to perform multivariable analysis of significant covariants. Results A total of 211 LSCC patients were included, of which 164 (77.7%) were male and 47 (22.3%) were female. Mean age was 62.19±8.328 years. A univariate analysis showed that seven factors including pathological differentiation, clinical stage, tobacco consumption, alcohol consumption, T stage, N stage, and concurrent chemoradiotherapy were correlated with survival (P<0.05). Cox proportional hazards regression analyses revealed that pathological differentiation (hazard ratio = 3.240, p=0.001), alcohol consumption (hazard ratio = 7.651, p =0.005), and concurrent chemoradiotherapy (hazard ratio = 2.090, P=0.046) were associated with OS in LSCC. Conclusions Pathological differentiation, alcohol consumption, and concurrent chemoradiotherapy are independent prognostic factors and predictors of recurrence in LSCC. These factors could help inform guidelines for clinical treatment and prognosis.